MicroRNAs and their role in breast cancer metabolism (review) - Lee, Wen Xuan; Yeo, Bann Siang; Mahmud, Rozi; Tan, Geok Chin; Abdul Wahid, Mohamed Ibrahim; Cheah, Yoke Kqueen (Spandidos Publications, 2024)
Breast cancer (BC) continues to be the leading cause of cancer-related mortality among women, placing a substantial disease burden on the global female population. MicroRNAs (miRNAs) are members of a large class of non-coding RNAs capable of regulating gene expression at the post-transcriptional level. With cases of early-onset BC on the rise, miRNAs are promising biomarkers and therapeutic targets for early BC detection and treatment. Dysregulated miRNA expression is known to be closely linked to BC development and metastasis in cancer cells via metabolic reprogramming. Normal cellular metabolism is tightly regulated by various complex signaling pathways. Therefore, dysregulation of metabolism due to metabolic reprogramming is considered a hallmark of cancer. The present review delves into the crucial roles that miRNAs serve in disordered cellular metabolism of BC by targeting gene transcripts, key metabolic enzymes and transporter proteins responsible for regulating major cellular metabolism pathways. The future outlook and clinical implications of miRNAs as potential diagnostic, prognostic and therapeutic markers in BC metabolism are also discussed.